Preparation method of ultrahigh-strength polyester industrial yarn
Through the blending reaction of large light low-viscosity polyester slices with dyeable polyester, capping agent and lubricant, combined with specific process parameters and equipment configuration, the in-production strength and stability of ultra-high-strength polyester industrial wire is solved. Problem, high strength and good mechanical properties of polyester industrial wire preparation are achieved.
Patent Information
- Application Number
- CN202411448591.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-31
AI Technical Summary
In the production of ultra-high strength polyester industrial wires, it is difficult to meet the requirements of high strength and dimensional stability at the same time. The commonly used tack enhancement methods will lead to melt rupture and molecular chain de-orientation, affecting fiber performance.
The large light low-viscosity polyester slices are blended with atmospheric cationic easy-to-dye polyester, end capping agent and lubricant, and are melted by screw, extruded by metering pump, slow cooling of the rear heater, side air cooling, cluster oiling, Pre-network, drafting and winding processes, combined with air wire guides and silk cake cooling devices, control temperature and pressure parameters, form molecular rope binding and nanoscale ion clusters, improving amorphous region orientation and creep resistance.
The preparation of ultra-high strength polyester industrial wire is achieved, with a strength of ≥9.5cN/dtex, which reduces molecular chain creep and melt rupture, and improves the mechanical and thermal resistance of the fibers.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing ultra-high-strength polyester industrial yarn, and belongs to the technical field of high-performance polyester. Background Art
[0002] As the most widely used fiber material in industrial textiles, polyester industrial yarn has good comprehensive properties such as high strength, large modulus, dimensional stability, and impact resistance. As a type of polyester industrial yarn, ultra-high-strength polyester industrial yarn is widely used in the fields of cables, ropes, and lifting belts due to its particularly high strength.
[0003] The strength of ordinary high-strength polyester industrial yarn produced in China is generally 7.8-8.2 cN / dtex. BG / T 16604-2017 "Polyester Industrial Filament" stipulates that the strength of ultra-high-strength polyester industrial yarn must be ≥8.2 cN / dtex. For example, CN112281272A uses polyester chips as raw materials, and obtains polyester cord fabric warp yarns with strength ≥8.4 cN / dtex and dimensional stability ≤6.2% through spinning, twisting, weaving and dipping heat treatment. In addition, polyester cord fabric warp yarns with the highest strength of 8.5 cN / dtex, elongation at break of 10.2%, EASL44.5N 5%, and shrinkage of 6.0% are specifically prepared. However, according to the dimensional stability DSI defined by it, it has reached 5%+6.0%=11%, that is, the dimensional stability is insufficient; CN101824664A adds a new chain extender C 15 H 16 N2O3, CN113430656A added nano-modified polytetrafluoroethylene to high molecular weight polyester to prepare ultra-high strength polyester industrial yarn. However, we found in production that due to the influence of various factors such as raw material quality and spinning process, when further improving the strength of polyester industrial yarn, especially exceeding the high standard of 9.0cN / dtex, we often encounter challenges such as poor spinning conditions and large fluctuations in strength performance. For example, the introduction of components such as the above-mentioned fluorine-containing compounds will not only cause certain safety issues in use, but also bring in small molecules that affect the stretching effect, resulting in an increase in terry yarn and breakage times.
[0004] Polyester can generally increase its molecular weight and fiber strength by increasing its viscosity, such as the common solid phase polycondensation viscosity increasing method. However, as the polymer molecular chain grows, the elastic deformation energy of the fluid in the spinneret hole becomes higher. When it reaches the flow energy required to overcome the viscous resistance, melt fracture is likely to occur. In the process, the fluidity of the melt is generally increased by increasing the temperature to avoid melt fracture. However, as the spinning temperature increases, the degradation of macromolecules intensifies, the product strength decreases, and the color turns yellow.
[0005] In the spinning process, in order to prepare ultra-high-strength polyester fibers, the orientation degree of the polyester amorphous region can also be increased by increasing the drafting multiple. Generally, the greater the orientation degree of the amorphous region, the higher the strength. However, the higher orientation degree of the amorphous region of the fiber is very prone to molecular chain deorientation, resulting in partial loss of strength.
[0006] During use, since only the hydrogen bond cross-linking points formed by ester groups between the molecular chains of ordinary polyester industrial silk act as network nodes, the hydrogen bonds are prone to dissociation and creep under stress. The macroscopic manifestation is stress relaxation and reduced fiber strength.
[0007] Therefore, it is of great significance to develop a polyester industrial yarn with ultra-high strength. Summary of the invention
[0008] In view of this, the present application provides a method for preparing ultra-high-strength polyester industrial yarn, which not only gives high-viscosity polyester chips a higher spinnability, but also achieves a viscosity drop of <0.15dL / g (i.e., the difference between the characteristic viscosity of the polyester chips before screw conveying and the characteristic viscosity of the polyester oil-free yarn after cooling and forming). During the production process, the average daily number of broken wires is ≤1.5 / bit, the average number of yarn cake hairs is ≤1 / spindle, and the finished yarn strength index is ≥9.5cN / dtex, meeting the requirements of ultra-high-strength polyester industrial yarn.
[0009] Specifically, the present application is implemented through the following scheme:
[0010] A method for preparing ultra-high-strength polyester industrial yarn, wherein the raw materials are melted by a screw, extruded by a metering pump, slowly cooled by a post-heater, cooled by side-blowing air, bundled and oiled, pre-interlaced, drawn and shaped, main interlaced, and wound to obtain ultra-high-strength polyester industrial yarn with a strength of ≥9.5 cN / dtex.
[0011] The raw material is obtained by solid phase thickening of low-viscosity polyester chips to 1.30±0.02dL / g, and then blending with normal pressure cationic easy-dyeing polyester (ECDP), a capping agent, and a lubricant. The intrinsic viscosity of the ECDP is 0.60±0.02dL / g, and the addition amount is 1.0-2.5wt%; the addition amount of the capping agent is 0.8-2.4wt%; and the addition amount of the lubricant is 0.4-1.4wt%.
[0012] The screw comprises six zones arranged in sequence, the temperature of zones 1 to 3 is 290 to 330°C, the temperature of zones 4 to 6 is 290 to 310°C, and the die pressure is 180 to 220 bar;
[0013] The temperature of the post heater is 350±10°C;
[0014] In the drafting and shaping process, the total drafting multiple (the speed ratio of GR-7+8 to GR-1+2) is 6.3 to 6.8;
[0015] In the drafting and shaping process, an air yarn guide is installed between GR-7+8 and GR-9+10;
[0016] The winding is provided with a yarn cake cooling device.
[0017] In the above scheme, the raw material is prepared by mixing high-viscosity polyester chips with ECDP, a capping agent, and a lubricant. Since ECDP has a smaller mean square gyration radius (greater curling degree) than PET at the same molecular weight, the physical cross-linking effect of the curling structure can be used to form molecular ropes to bind the molecular chains in the amorphous region of the linear polyester, which is beneficial to increase the interaction between the molecular chains in the amorphous region and the maintenance of the oriented structure, reduce the slippage between the molecular chains, and effectively improve the strength and creep resistance of the ultra-high-strength industrial yarn, so that it still maintains ultra-high strength when used above the glass transition temperature. At the same time, there are sulfonates on the side chains of ECDP, and the introduction of hydrophilic ionic groups will lead to the ionomer main chain and the ionic side groups. Microphase separation occurs, forming nanoscale ion clusters, giving the ionomer a unique molecular chain structure and macroscopic properties. This physical crosslinking can greatly improve the strength and toughness of the polymer; the addition of end-capping agents effectively improves the hydrolysis resistance and heat resistance of polyester molecular chains, reduces the degradation reaction during the screw melt extrusion process, and reduces the viscosity drop; the addition of lubricants is conducive to reducing the friction between the high-viscosity polyester melt and the screw, reducing the thermal degradation caused by local friction overheating. In addition, lubricants can improve the melt flow and spinning difficulties caused by the increase in molecular weight, and improve spinnability; the relatively high setting of the post-heater temperature, combined with the setting of the screw melting parameters, is conducive to the extrusion of the melt from the component and improves spinnability. The use of air guides and yarn cake cooling devices can effectively and quickly reduce the yarn cake temperature to below the glass transition temperature, reduce the strength loss caused by molecular chain creep, and the strength of the polyester industrial yarn produced can reach 9.5cN / dtex and above.
[0018] Further, as a preference:
[0019] In the solid phase viscosity increasing process, the vacuum degree of the drum is controlled to be less than 80 Pa, and the temperature is raised in stages for reaction. The parameters of each stage are set as follows:
[0020] Stage 1: within 120 to 150 minutes, the temperature is raised from room temperature to 105±5℃, and the temperature is kept for pre-crystallization for 150 to 200 minutes;
[0021] Stage 2: within 330 to 430 minutes, the pre-crystallization temperature is raised to 180±5°C, and the crystallization is kept at this temperature for 150 to 200 minutes;
[0022] In the third stage, the crystallization temperature is raised to 220±5°C within 200 to 260 minutes, and the reaction is kept warm for 1100 to 1300 minutes.
[0023] The solid-phase viscosity increasing process with staged heating uses a rotary drum to heat the polyester chips in stages, thereby achieving a step-by-step and stable increase in the viscosity of the chips.
[0024] The side-blowing air temperature is 20±1° C., the wind speed is 0.6±0.1 m / s, and the relative humidity is 80±15%.
[0025] The cluster oiling is carried out by oil nozzle.
[0026] The pre-network pressure is 1.5±0.5 bar, so that the effective components of the spinning oil can fully enter the interior of the filament bundle.
[0027] The pressure of the main network is 2.5±0.5 bar, which gives the tows certain network nodes to prevent divergence.
[0028] The drafting ratio and temperature of each hot roller in the drafting setting are as follows:
[0029] First-stage hot roller drafting: 1.0-1.2 times, 85-105°C;
[0030] Secondary hot roller drafting: 2.0-5.0 times, 100-150℃;
[0031] Three-stage hot roller drafting: 1.0-3.0 times, 200-240℃;
[0032] Setting: 0.9~1.1 times, 150~240℃.
[0033] The winding speed is 2500-3200 m / min.
[0034] The pressure of the air yarn guide is 0.5-4.0 bar, and preferably 3.0±0.5 bar, which has a better cooling effect on the yarn bundle.
[0035] The wind speed for cooling the silk cake is 1.0-6.0 m / s, and preferably 4.0±0.5 m / s, and the wind temperature is 20±2°C.
[0036] The end-capping agent is one or a mixture of acetic acid, ethylene oxide, and propylene oxide, and ethylene oxide is preferred.
[0037] The lubricant is one or a mixture of pentaerythritol tetrastearate (PETS), TAF, dioctyl phthalate (DOP), di(2-ethyl)hexyl terephthalate (DEHTP), and TAF is preferred.
[0038] The amount of ECDP added is 2.0±0.2wt%; the amount of end-capping agent added is 1.5±0.2wt%; the amount of lubricant added is 0.8±0.2wt%
[0039] The beneficial effects of this application are as follows:
[0040] 1. The present invention uses bright polyester chips as the basic raw material, adds ECDP, end-capping agent, and lubricant, and the molecular chain structure of ECDP and the physical cross-linking effect of ion clusters formed by sulfonates can greatly improve the strength and toughness of the polymer; the addition of the end-capping agent can reduce the thermal degradation of the melt and improve the hydrolysis resistance and thermal stability of the product; the addition of the lubricant can reduce the local overheating degradation of the melt caused by friction, and also reduce the possibility of melt rupture during melt extrusion, thereby improving spinnability.
[0041] 2. In the melt extrusion process, reactive blending and melt blending are used in melt preparation. The combination of post-heater and melt extrusion is conducive to the extrusion of the melt from the component and improves the spinnability.
[0042] 3. In the spinning and shaping process, an air wire guide is installed between GR-7+8 and GR-9+10, which can quickly cool down the filament bundle and reduce the molecular chain disorientation due to excessive temperature, thereby stabilizing the strength index; a wire cake cooling device is installed under the winding stand, which can cool the wire cake during the winding process and reduce the molecular chain disorientation in the amorphous area due to excessive temperature, thereby stabilizing the strength index; the above-mentioned air wire guide and wire cake cooling device can quickly reduce the temperature of the wire cake to below the glass transition temperature, reduce the strength loss caused by molecular chain creep, and the compressed air and cold air work together to cool down. The process modification is simple, the cost is low, and it is easier to promote on a large scale. DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application are further described in detail below. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0044] Example 1
[0045] This embodiment is a method for preparing ultra-high-strength polyester industrial yarn, using high-gloss polyester chips as the basic raw material, with an intrinsic viscosity of 0.682 dL / g, a terminal carboxyl group of 26.3 mol / t, a DEG of 0.95%, a b value of 3.2, a moisture content of 0.1%, and dust <500 ppm. The specific process is as follows:
[0046] Step 1: The bright polyester chips are subjected to drum solid phase polycondensation to increase viscosity. The vacuum degree of the drum is 60 Pa. The viscosity increasing process is as follows:
[0047] (1) Pre-crystallization stage: the pre-crystallization temperature is 107°C, the time from room temperature to the pre-crystallization temperature is 130 min, and the heat preservation time at the pre-crystallization temperature is 180 min;
[0048] (2) Crystallization stage: crystallization temperature is 182°C, the time from pre-crystallization temperature to crystallization temperature is 350 min, and the heat preservation time at crystallization temperature is 160 min;
[0049] (3) Reaction stage: reaction temperature is 217°C, the time from crystallization temperature to reaction temperature is 220 min, and the heat preservation time at reaction temperature is 1200 min.
[0050] The intrinsic viscosity of the slices obtained by thickening is 1.312 dL / g, the terminal carboxyl group is 10.7 mol / t, the DEG is 1.11%, the b value is 4.8, the moisture content is less than 200 ppm, and the dust is less than 500 ppm.
[0051] Step 2, mixing the slices obtained by viscosity enhancement with ECDP, a capping agent and a lubricant to obtain a raw material.
[0052] The addition amount of ECDP (commercially available) is 2.1 wt%, and the core parameters include: intrinsic viscosity of 0.60 dL / g, terminal carboxyl group of 4.2 mol / t, DEG of 3.9%, b value of 5.2, moisture <200 ppm, and dust <500 ppm.
[0053] The end-capping agent is ethylene oxide, and the added amount is 1.6 wt%.
[0054] The lubricant is TAF, and the added amount is 0.7wt%.
[0055] The rest are slices obtained by viscosity enhancement, with an addition amount of 95.6%.
[0056] The blending reaction temperature is 280°C and the duration is 5 minutes.
[0057] Step three, the raw materials are melted by screw, extruded by metering pump, slowly cooled by post-heater, cooled by side blowing, bundled and oiled, pre-networked, drawn and shaped, and wound by main network to obtain ultra-high strength polyester industrial yarn with a specification of 1130dtex / 192f.
[0058] The temperatures of screw zones 1 to 6 are: 298℃, 308℃, 300℃, 295℃, 293℃, 291℃, and the head pressure is 195bar.
[0059] The box temperature is 300℃; the metering pump specification is 20cc / rev, 13.20rpm; the filter accuracy of the spinning component is 20 mesh; the post-heater temperature is 350℃; the component spinneret specification is 0.6×1.2 / 192; the side blowing wind speed is 0.6m / s, the temperature is 20±1℃, and the humidity is 80±15%.
[0060] The oil pump specification is 0.3cc / rev and the speed is 37r / min.
[0061] The pressure of the pre-network device is 1.6 bar.
[0062] The pressure of the main network device is 2.7 bar.
[0063] The air guide is installed between GR-7+8 and GR-9+10, with a pressure of 2.8 bar.
[0064] The yarn cake cooling device is located directly below the winder, with a wind speed of 4.1m / s and a wind temperature of 20±2℃ to cool the yarn cake.
[0065] The parameter settings of each drafting roller in spinning are shown in Table 1.
[0066] Table 1: Process parameters of spinning drafting roller
[0067]
[0068]
[0069] The spinning condition in the above production process is good, the average number of broken silks per day is 1.2 per bit, the average number of silk cake hairs is 0.6 per spindle, the fiber forming is normal, the oil content is 0.54%, the viscosity of oil-free silk is 1.177dL / g, and the viscosity is reduced to 0.135dL / g. The finished ultra-high-strength polyester industrial yarn has good mechanical properties, with a fineness of 1128.6dtex, a breaking strength of 109.7N, a breaking strength of 9.72cN / dtex, a breaking elongation of 11.53%, a dry heat shrinkage of 7.64%, and a network degree of 6.6 / m.
[0070] Example 2
[0071] The configuration of this embodiment is the same as that of embodiment 1, except that the addition amount of ECDP is selected as 0.0wt% (i.e., no ECDP is added), 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, and 3.5wt%, respectively. The results are shown in Table 2.
[0072] Table 2: Effect of ECDP addition on the preparation of polyester industrial yarn
[0073]
[0074] Comparative Example 1 and Table 2 show that:
[0075] When ECDP is not added to the raw materials or its addition amount is too low or too high, the strength of the industrial yarn decreases. This is mainly because after the industrial yarn is wound, the temperature of the inner layer of the silk cake is above the glass transition temperature, and the molecular chain curling structure and ion clusters of ECDP can act as physical cross-linking, which greatly reduces the slip between molecular chains and reduces the loss of strength. But overall, when the addition amount of ECDP is too low (<1.0wt%), the molecular chain slips more obviously, the strength is slightly lost, which is 9.4~9.6cN / dtex, and the number of silk cake hairs is 0~1 strands / spindle; when the addition amount of ECDP is too high (>2.5wt%), due to the low viscosity of ECDP itself, the molecular chain is relatively short, which is not conducive to the orientation of molecules in the amorphous region, so the strength loss and spinning condition are more obvious, which is 9.1~9.3cN / dtex, and the number of silk cake hairs increases to 1~3 strands / spindle. Therefore, in the reaction system of the present application, the addition amount of ECDP is appropriately controlled within the range of 1.0 to 2.5 wt %, and preferably 2.0±0.2 wt %.
[0076] Example 3
[0077] The configuration of this embodiment is the same as that of embodiment 1, except that the addition amounts of the end-capping agent ethylene oxide are 0.0wt% (i.e., no ethylene oxide end-capping is added), 0.4wt%, 0.8wt%, 1.2wt%, 2.0wt%, 2.4wt%, 2.8wt%, and 3.2wt%, respectively. The results are shown in Table 3.
[0078] Table 3: Effect of end-capping agent addition on the preparation of polyester industrial yarn
[0079]
[0080] Comparative Example 1 and Table 3 show that:
[0081] When the amount of ethylene oxide, the end-capping agent, in the raw material is too low or too high, the strength of the industrial yarn will decrease. Ethylene oxide can improve the hydrolysis resistance and heat resistance of the polyester molecular chain, reduce the degradation reaction during the screw melt extrusion process, and reduce the viscosity drop. Specifically, when the amount of ethylene oxide added is too low (<0.8wt%), the degradation of the macromolecular chain is more obvious, the viscosity of the oil-free yarn is <1.019dL / g, the viscosity drop is >0.29dL / g, the strength is slightly lost, which is 9.5~9.6cN / dtex, and the number of silk cake hair is 0~1 root / ingot; when the amount of ethylene oxide added is too high (>2.4wt%), due to excessive addition of ethylene oxide, the additive is a small molecular impurity for the high molecular polymer, the number of silk cake hair increases to 1~2 roots / ingot, and the strength loss is obvious, which is 9.0~9.2cN / dtex. Therefore, in the reaction system of the present application, the amount of the end-capping agent added is appropriately controlled at 0.8-2.4 wt %, and preferably 1.5±0.2 wt %.
[0082] In the above scheme, replacing the end-capping agent with propylene oxide or acetic acid shows the same effect as ethylene oxide. Relatively speaking, ethylene oxide is slightly better in improving the anti-hydrolysis performance and heat resistance.
[0083] Example 4
[0084] The configuration of this embodiment is the same as that of embodiment 1, except that the amounts of TAF added are 0.0wt% (i.e., no TAF lubrication), 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, and 1.4wt%, respectively. The results are shown in Table 4.
[0085] Table 4: Effect of lubricant addition on the preparation of polyester industrial yarn
[0086]
[0087] Comparative Example 1 and Table 4 show that:
[0088] When the amount of TAF is small (<0.6wt%), it exhibits internal lubrication performance. Since internal lubrication only reduces the interaction between macromolecules, there is still a large friction between the melt and the screw, the wall, and the components, causing local overheating and degradation of the melt. The small molecules of local degradation have little effect on the viscosity drop of the melt, but have a greater impact on the strength of the finished yarn. The viscosity drop is <0.15dL / g, and the strength is 9.1-9.3cN / dtex. In addition, during the production process, the high viscosity of the slices has a certain impact on the spinning conditions: the spinning pressure is greater than 230bar, the spinneret does not discharge the yarn smoothly, the average number of broken ends per day is 2-4 / bit, and the number of hairy yarns is 2-5 / spindle.
[0089] When the amount of TAF slightly exceeds the compatibility limit (TAF is 0.6-1.0wt%), a thin film can be formed on the interface, which significantly reduces the flow resistance. The spinning conditions and physical properties are similar to those in Example 1.
[0090] When the amount of TAF is 1.2-1.4wt%, the strength decreases slightly to 9.4-9.5cN / dtex, and the other indicators are similar to those in Example 1.
[0091] In the above scheme, the lubricants are replaced by pentaerythritol tetrastearate (PETS), dioctyl phthalate (DOP), and di(2-ethyl)hexyl terephthalate (DEHTP), respectively, which show the same effect as TAF. Relatively speaking, TAF is slightly better in reducing the force between macromolecules.
[0092] Example 5
[0093] The configuration of this embodiment is the same as that of Embodiment 1, except that the pressures of the air yarn guide are 0.0 bar (i.e., no air yarn guide), 0.5 bar, 1.0 bar, 1.5 bar, 2.0 bar, 2.5 bar, 3.0 bar, 3.5 bar, and 4.0 bar, respectively. The results are shown in Table 5.
[0094] Table 5: Effect of air guide pressure on polyester industrial yarn preparation
[0095]
[0096]
[0097] Comparative Example 1 and Table 5 show that:
[0098] The air yarn guide is installed between GR-7+8 and GR-9+10, and compressed air is mainly used to cool the yarn bundle, so that the yarn bundle is quickly reduced to below the glass transition temperature, reducing the strength loss caused by molecular chain creep. In the experiment, as the compressed air pressure increased from 0.0 bar to 3.5 bar, the industrial yarn strength gradually increased from 9.5 cN / dtex to 9.7 cN / dtex, and the other indicators were the same as in Example 1. However, when the pressure was 4.0 bar, due to the high pressure and low yarn bundle temperature, the yarn bundle on GR-9+10 shook significantly, causing slight friction between the yarn bundles in adjacent yarn paths, and slight hairy yarns appeared on the yarn cake (about 1 to 3 strands / spindle), and the other indicators were the same as in Example 1.
[0099] Example 6
[0100] The configuration of this embodiment is the same as that of embodiment 1, except that the wind speeds for cooling the silk cakes are 0.0 m / s (i.e., no silk cake cooling), 1.0 m / s, 2.0 m / s, 3.0 m / s, 4.0 m / s, 5.0 m / s, and 6.0 m / s, respectively. The results are shown in Table 6.
[0101] Table 6: Effect of cooling air speed on the preparation of polyester industrial yarn
[0102]
[0103] Comparative Example 1 and Table 6 show that:
[0104] The silk cake cooling device can directly cool the silk cake during the winding process. When the wind speed is between 0.0 and 3.0 m / s, as the wind speed gradually increases, the product strength gradually increases from 9.3 cN / dtex to 9.7 cN / dtex. When the wind speed is between 4.0 and 6.0 m / s, the strength improvement is not obvious, which is 9.65 to 9.75 cN / dtex. The size of the silk cake cooling wind has no effect on the number of silk cake fibers, which is 0 to 1 per ingot.
[0105] In the above scheme, when the air yarn guide pressure is 0.0 bar and the yarn cake cooling wind speed is 0.0 m / s, it is equivalent to not installing the air yarn guide and not turning on the yarn cake cooling wind, resulting in the yarn bundle being above the glass transition temperature for a long time after winding, and the molecular chain creeping is serious. The final fiber strength after drawing and shaping is only maintained at 9.20 cN / dtex, which is much lower than the breaking strength of Example 1.
[0106] It can be seen from the above Examples 1 to 6 that in the preparation scheme provided in the present application, the core parameters affecting the spinning conditions and breaking strength include: ECDP, capping agent, TAF, post-heater temperature, air guide pressure, and yarn cake cooling parameters (mainly wind speed), wherein the order of influence of each parameter is: TAF>post-heater temperature>yarn cake cooling parameters>ECDP>air guide pressure>capping agent.
[0107] Comparative Example 1
[0108] The configuration of this comparative example is the same as that of Example 1, except that the raw materials used for spinning are only high-viscosity polyester chips and TAF (added in an amount of 0.7 wt%), and no air guide and yarn cake cooling device are provided.
[0109] In the above production process, the average number of broken wires per day was 4.5 per bit, the average number of silk cake hairs was 5.6 per spindle, the fiber formation was normal, the oil content was 0.53%, the viscosity of oil-free yarn was 1.008dL / g, and the viscosity dropped to 0.304dL / g. The finished ultra-high-strength polyester industrial yarn had a fineness of 1125.1dtex, a breaking strength of 99.1N, a breaking strength of 8.81cN / dtex, a breaking elongation of 12.02%, a dry heat shrinkage of 7.54%, and a network degree of 6.7 / m.
[0110] Compared with Example 1, it can be seen that only by adding TAF, the strength of the finished yarn is reduced from 9.72 cN / dtex in Example 1 to 8.81 cN / dtex in the comparative example, and the decrease is very obvious. This shows that in the process of realizing the ultra-high strength of the polyester industrial yarn in this case, in addition to the viscosity increase and spinning process (including but not limited to the screw extrusion temperature and the post-heater temperature), ECDP, end capping agent, lubricant, air guide, yarn cake cooling device and other factors are also needed to work together to achieve it.
[0111] Comparative Example 2
[0112] The configuration of this comparative example is the same as that of Example 1, except that the temperature of the post-heater is 310°C.
[0113] Compared with the higher heater temperature (350°C) in Example 1, the post-heater temperature in this comparative example is slightly higher than the extrusion melt temperature. Due to the high melt viscosity, the melt extruded in the spinning assembly may break, resulting in an increase in the frequency of broken ends and hairy fibers, affecting spinnability.
[0114] Comparative Example 3
[0115] This comparative example is the same as Example 1, except that TAF is replaced by nano-modified polytetrafluoroethylene, and the nano-modified polytetrafluoroethylene is prepared by using the polytetrafluoroethylene nanoparticles containing ester groups on the surface according to the scheme of Example 6 in CN113430656A. However, since the polytetrafluoroethylene nanoparticles are not commercially available, they need to be prepared by a special modification process: a chlorobenzene solution with a volume content of 37.5% methacrylate is prepared, polytetrafluoroethylene nanopowder is placed in the above solution, and treated with plasma in an argon atmosphere, so that methacrylate is chemically grafted and polymerized on the surface of the polytetrafluoroethylene nanopowder, and a layer of grafted polymer is formed on the surface, thereby obtaining polytetrafluoroethylene nanoparticles containing ester groups on the surface with an average particle size of 300nm and an ester group content of 20ppm.
[0116] From the above process, we can see that: regardless of whether the nanoparticles can guarantee the stability of performance between batches, the preparation process alone is relatively complicated and the cost is high and cannot be mass-produced.
[0117] The reagents used in this case are all commercially available and have high universality. From the perspective of the coordination of the raw material composition, the TAF added in the mixed reaction not only reduces the interaction between macromolecules and achieves internal lubrication, but also forms a thin film on the interface, reducing the possibility of melt rupture during melt extrusion, significantly reducing flow resistance and improving spinning conditions; and the end-capping of the molecular chain by the end-capping agent, the molecular chain orientation maintained by ECDP, and the reduction of the creep of the molecular chain after winding through the air yarn guide and cooling device effectively improve the strength of the industrial yarn.
[0118] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A method for preparing ultra-high-strength polyester industrial yarn, characterized in that: The raw materials are melted by screw, extruded by metering pump, slowly cooled by post-heater, cooled by side-blowing, bundled and oiled, pre-interlaced, drawn and shaped, main interlaced, and wound to obtain ultra-high-strength polyester industrial yarn with a strength of ≥9.5 cN / dtex. The raw material is obtained by solid phase thickening of low-viscosity polyester chips to 1.30±0.02 dL / g, and then blending with normal pressure cationic easy-to-dye polyester, end-capping agent and lubricant. The intrinsic viscosity of the ECDP is 0.60±0.02 dL / g, and the addition amount is 1.0-2.5 wt%; the addition amount of the end-capping agent is 0.8-2.4 wt%; the addition amount of the lubricant is 0.4-1.4 wt%; The screw comprises six zones arranged in sequence, the temperature of zones 1 to 3 is 290 to 330°C, the temperature of zones 4 to 6 is 290 to 310°C, and the die pressure is 180 to 220 bar; The temperature of the post heater is 350±10°C; In the drafting and shaping process, the total drafting multiple is 6.3-6.8; An air yarn guide is provided in the drafting and shaping process; A yarn cake cooling device is provided in the winding process.
2. The method for preparing ultra-high-strength polyester industrial yarn according to claim 1, characterized in that: In the solid phase viscosity increasing process, the vacuum degree of the drum is controlled to be less than 80 Pa, and the temperature is raised in stages for reaction. The parameters of each stage are set as follows: Stage 1: within 120-150 min, the temperature is raised from room temperature to 105±5°C, and the temperature is kept for pre-crystallization for 150-200 min; Stage 2: within 330-430 min, the pre-crystallization temperature is raised to 180±5°C, and the crystallization is kept at this temperature for 150-200 min; In stage three, the crystallization temperature is raised to 220±5°C within 200-260 min, and the reaction is kept warm for 1100-1300 min.
3. The method for preparing ultra-high-strength polyester industrial yarn according to claim 1, characterized in that: The side-blowing air temperature is 20±1°C, the wind speed is 0.6±0.1 m / s, and the relative humidity is 80±15%.
4. The method for preparing ultra-high strength polyester industrial yarn according to claim 1, characterized in that: The pre-network pressure is 1.5±0.5 bar.
5. The method for preparing ultra-high-strength polyester industrial yarn according to claim 1, characterized in that: The pressure of the main network is 2.5±0.5 bar.
6. The method for preparing ultra-high-strength polyester industrial yarn according to claim 1, characterized in that: The drafting ratio and temperature of each hot roller in the drafting setting are as follows: First-stage hot roller drafting: 1.0-1.2 times, 85-105°C; Secondary hot roller drafting: 2.0-5.0 times, 100-150°C; Three-stage hot roller drafting: 1.0-3.0 times, 200-240°C; Setting: 0.9-1.1 times, 150-240 ℃; The winding speed is 2500~3200 m / min.
7. The method for preparing ultra-high-strength polyester industrial yarn according to claim 1, characterized in that: The pressure of the air thread guide is 0.5-4.0 bar.
8. The method for preparing ultra-high strength polyester industrial yarn according to claim 1, characterized in that: The wind speed for cooling the silk cake is 1.0-6.0 m / s, and the wind temperature is 20±2°C.
9. The method for preparing ultra-high-strength polyester industrial yarn according to any one of claims 1 to 8, characterized in that: The end-capping agent is one or a mixture of acetic acid, ethylene oxide and propylene oxide.
10. The method for preparing ultra-high strength polyester industrial yarn according to any one of claims 1 to 8, characterized in that: The lubricant is one or a mixture of pentaerythritol tetrastearate, TAF, dioctyl phthalate, di(2-ethyl)hexyl terephthalate.
